The Potential for REE and associated critical metals in coastal sand (placer) deposits of Greece: a review - Papadopoulos, Argyrios; Tzifas, Ioannis; Tsikos, Harilaos (Minerals, 2019)
The rare earth elements (REEs) are characterized by the European Union (EU) as critical raw materials with a significant risk of supply because of their broad utility in both traditional and emerging technological applications. The growing demand for REE has caused a flurry in the search for new REE deposits in Europe and elsewhere in the world, and is also linked to rising exploitation efforts in a variety of geological settings. To this end, Greece appears to be a promising candidate to become a leading EU country in terms of REE by virtue of its natural endowment in sedimentary heavy mineral deposits (placers) along its long coastline. The present review focuses on the distribution, abundance, and bulk geochemistry of REEs and other critical metals (Ta, Nb, Co) associated with placer deposits of Greece, and specifically with geologically young heavy mineral sand accumulations developed proximal to felsic plutonic source rocks. These deposits are also enriched in the actinides uranium (U) and thorium (Th), as both of these metals are typically associated with REE-rich minerals such as xenotime, monazite, thorite, allanite, and zircon. Previous studies have employed a variety of analytical techniques down to nano-meter scale with the aim to elucidate the mineralogy and distribution of REE and associated actinides in Greek beach placers. In view of this mineralogically-intensive background, the present review focuses chiefly on bulk geochemical characteristics of the same deposits and the variations thereof between two major geographical regions (northern Greece, southern Aegean) and across individual placer occurrences within them. In this framework, we present comprehensive compositional comparisons between the different deposits, highlighting the geological sub-environments wherein they occur, their distinctive sources and geochemical signatures, and their potential economic significance in terms of REE and other critical metal enrichments where applicable.